Epictetusian Rationality and Evolutionary Stability - Gregory Ponthiere (Global Labor Organization (GLO), 2023)
An economic interpretation of Epictetus's precept of 'Taking away aversion from all things not in our power' consists of extending the do- main of indifference beyond its boundaries under non-ethical preferences, so as to yield indifference between outcomes differing only on things out- side one's control. This paper examines the evolutionary dynamics of a population composed of Nash agents and Epictetusian agents matched randomly and interacting in the prisoner's dilemma game. It is shown that, whether or not the types of players are common knowledge, nei- ther the Nash nor the Epictetusian type is an evolutionary stable strategy under perfectly random matching. However, if the matching process ex- hibits a suffi ciently high degree of assortativity, the Epictetusian type is an evolutionary stable strategy, and drives the Nash type to extinction.
Keywords: C73; C62; D60; 330; ethical preferences; evolutionary stability; cooperation; prisoner's dilemma; Epictetus